Peroneal Intraneural Ganglion Cyst Arising from Proximal Tibiofibular Joint: Advantages of Magnetic Resonance Imaging on Preoperative Diagnosis - Maras Ozdemir, Zeynep; Sagir Kahraman, Aysegul; Karakaplan, Mustafa; Topgul, Haldun; Ayse Gormeli Meryem Merve Hamurcu, Cemile (Annals of Medical Research, 2021)
None
Keywords: Ganglion Cyst; Peroneal Nerve; Superior Tibiofibular Joint; Magnetic Resonance Imaging.